2002
DOI: 10.1021/jp026285e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Conductance Behavior of Carbon-Based Molecular Junctions with Conjugated Structures

Abstract: A novel molecular junction based on a monolayer between carbon and mercury “contacts” was investigated by examining current/voltage behavior as a function of temperature and monolayer thickness. Monolayers of phenyl, biphenyl, and terphenyl were covalently bonded to flat, graphitic carbon, then a top contact was formed with a suspended mercury drop. Similar molecular junctions were formed from multilayer nitroazobenzene (NAB) films of 30 Å and 47 Å thickness, and junctions were examined over the temperature ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 45 publications
7
96
0
Order By: Relevance
“…16,21,37,38 RESULTS AND DISCUSSION these values agree with previous experimental reports using single-molecule and large-area junctions. 27,[38][39][40][41][42][43][44][45] These results presented here also agree with theoretical calculations by Ratner and coworkers; these authors predict (using density functional theory, DFT) a value of  = ~0.3 Å -1 for SAMs of polyphenyldithiolates by assuming a continuous conjugation of the molecules with the metal electrodes. 17 We compared the electrical properties of SAMs of SPh n to SAMs of C≡CPh n on Au TS (Figure 2b).…”
Section: Introductionsupporting
confidence: 91%
“…16,21,37,38 RESULTS AND DISCUSSION these values agree with previous experimental reports using single-molecule and large-area junctions. 27,[38][39][40][41][42][43][44][45] These results presented here also agree with theoretical calculations by Ratner and coworkers; these authors predict (using density functional theory, DFT) a value of  = ~0.3 Å -1 for SAMs of polyphenyldithiolates by assuming a continuous conjugation of the molecules with the metal electrodes. 17 We compared the electrical properties of SAMs of SPh n to SAMs of C≡CPh n on Au TS (Figure 2b).…”
Section: Introductionsupporting
confidence: 91%
“…1͑d͒. Indeed, Anariba and Mcreery have shown that the current magnitude through a twisted terphenyl structure is lower than through the planar structure, 21 again validating our idea that qualitative trends in molecular conductances can be predicted using this simple model and the ideas of delocalization and symmetry breaking.…”
Section: Breaking Symmetry: Rotating the Central Phenyl Ringsupporting
confidence: 74%
“…2C). [69,[136][137][138] Related paradigms involve using eutectic Ga/In (eGaIn, melting point $16 8C) on SAMs at Ag, [139] Hg on adlayers bonded to flat carbon, [71,72,140] and Hg on a molecular layer at silicon. [141] A liquid metal top contact circumvents the use of vapor phase atoms, so metal incursion into the molecular layer is less likely.…”
Section: Progress With Ensemble Molecular Junctionsmentioning
confidence: 99%